THE CYTOTOXICITY EFFECTS OF OUTER MEMBRANE VESICLES ISOLATED FROM HOSPITAL AND LABORATORY STRAINS OF PSEUDOMONAS AERUGINOSA ON HUMAN KERATINOCYTE CELL LINE - Almashgab, Ali M.; Yahya, Esam Bashir; Banu, Afreen (Malaysian Journal of Science, 2020)
The pathogenicity of Pseudomonas aeruginosa gained from secreting virulence factors called Outer membrane vesicles (OMVs), this study aimed to determine the concentration of OMVs of two strains of P. aeruginosa and estimate the cytotoxicity effects of the isolated vesicles on human keratinocyte cell line HaCaT biomass. OMVs isolated from hospital strain was higher than from laboratory strain which support that hospital strain is more toxic than laboratory strain, the highest OMVs detected was from laboratory strain treated with Gentamicin, the response to the antibiotic stimulated the bacteria to secrete more virulence factors seeking for protection. The toxicity caused by Outer membrane vesicles showed a loss of biomass in hospital strain and a slight increase of biomass in laboratory strain, and that is another evident that hospital strain are more toxic than lab strain. The biomass and pictures illustrated that the cells still growing rapidly when it treated with low concentration of OMVs.